Comparing Screening Abilities of the 33-Item Hypomania Checklist (HCL-33) and the 33-Item Hypomania Checklist External Assessment (HCL-33-EA) for the Detection of Bipolar Disorder - Wang, Yuan-Yuan; Feng, Yuan; Fang, Meng; Guo, Chengwei; Ungvari, Gabor S.; Hall, Brian J.; Wang, Gang; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Bipolar disorder (BD) is a severe psychiatric disorder that is often misdiagnosed and under-diagnosed in clinical settings. The 33-item Hypomania Checklist (HCL-33) is a newly developed self-administered scale for BD detection, while the 33-item Hypomania Checklist-external assessment (HCL-33-EA) is a version of HCL-33 for external rating used by patient’s carer (e.g., family member or friend). We aimed to compare the screening abilities between the HCL-33 and the HCL-33-EA, and evaluate the screening consistency between the two scales. Methods: The data was collected from 269 patients with diagnosed BD (n = 84) or major depressive disorder (MDD) (n = 185). The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the curve (AUC) between the HCL-33 and the HCL-33-EA for BD were compared against clinician diagnosis as the gold standard. Results: Using Youden’s index, the HCL-33-EA showed a better performance than the HCL-33 (1.51 vs. 1.41). The HCL-33-EA was more sensitive in correctly identifying BD patients from MDD patients than the HCL-33 (0.83 vs. 0.59), while the HCL-33 presented better specificity than the HCL-33-EA (0.82 vs. 0.68). There was significant screening consistency between the two scales (p < 0.001). Conclusions: Both scales have good screening abilities, and are useful instruments for the identification of BD in clinical settings.